(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate and compare the clinical and radiological outcomes of patients aged >40 years and ≤40 years old, who underwent open reduction internal fixation for posterior fracture and/or fracture dislocation of the acetabulum.Material and Methods: A total of 52 patients who underwent surgical treatment for posterior acetabular fracture and/or fracture dislocation between June 2006 and October 2013 were included in this study. The patients were divided into the following 2 groups: group I, patients aged 40 years (n = 27; mean age, 53.3; mean follow-up period, 36.8 months). The Judet–Letournel classification system was used in the radiological classification of acetabular fractures. Clinical and radiological evaluations were performed using the modified Merle D’Aubigne evaluation score and the criteria developed by Matta, respectively. In addition, radiological evaluation for heterotopic ossification was performed according to the Brooker scoring system.Results: No significant difference in the quality of reduction and clinical and radiological findings was found between the two groups (p>0.05). The modified Merle D’Aubigne clinical outcome distribution and the distribution of Matta radiological results in groups I and II did not differ significantly (p>0.05 and p>0.05, respectively). Moreover, no significant difference in the development of postoperative heterotopic ossification was observed between the groups (p>0.05). Conclusion: Clinical and radiological outcomes are not significantly different between patients younger and those older than 40 years. Nevertheless, the clinical outcome scores are better in patients aged ≤40 years.